Study of Langerhans cells and T lymphocytes in vulvar lichen sclerosus lesions. (16th December 2020) - Bao, Yingqiu; Li, Ziyuan; Liu, Wan; Fu, Yu; Lv, Jiaqi; Sun, Kailv; Chang, Jianmin
Abstract: Background: The aetiology and pathogenesis of vulvar lichen sclerosus (LS), a chronic inflammatory disease, is not completely clear. It has been found that local cellular immune abnormalities play an important role in the immune mechanism of LS, mainly characterised by abnormal numbers of Langerhans cells in the epidermis and abnormal numbers of dermal T lymphocytes. Objective: To evaluate the densities of Langerhans cells and T‐lymphocyte subpopulations in vulvar LS. Methods: The density of Langerhans cells in the epidermis, and CD3 +, CD4 + and CD8 + T cells in the dermis of seven early‐stage and eight late‐stage cases of vulvar LS were detected with direct immunofluorescence, and compared with 15 normal controls. Results: The density of Langerhans cells in the late‐stage group was significantly higher than in the normal group ( P = 0.001). The densities of CD3 +, CD4 + and CD8 + T lymphocytes in both the early‐ and late‐stage (deeper dermis) groups were higher than in the normal group (P < 0.05). The ratio of CD4 + /CD8 + T lymphocytes in the early‐stage and normal groups showed no significant difference ( P = 0.151), while the late‐stage (deeper dermis) groups decreased significantly compared with early‐stage, late‐stage (upper dermis) and normal groups (P < 0.001). Conclusion: The densities of Langerhans cells, CD3 +, CD4 + and CD8 + T cells, and the ratio of CD4 + /CD8 + T lymphocytes were different in different stages of LS, which supports the important role of cellular immunity in mechanisms of LS.